The Influence Of The Implementation Of Information Technology And Accounting Information System On Company Performance - Karimah, Maulidia Fathinul Isy; Suwandi, Suwandi (Indonesian Vocational Research Journal, 2025)
The purpose of this study is to evaluate and show how accounting information systems and information technology affect company performance. The quantitative approach in this study uses primary data. A total of 42 workers from Semen Indonesia Group were selected as samples for this study. Google form is used as a data collection tool to provide questionnaires to respondents. By using SPSS, the data analysis method uses multiple linear regression. According to the findings of this study, information technology improves company performance. However, company performance is not affected by accounting information systems. Information technology is included in the category of very good company performance, according to the results of research responses from respondents. While the accounting information system needs to be considered again in order to improve company performance properly. This study can also be used by companies to influence company performance and productivity.